2009
DOI: 10.4319/lo.2009.54.1.0344
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics of seston: A recurring nighttime peak and seasonal shifts in composition in a stream ecosystem

Abstract: We measured the baseflow concentration and composition of seston and suspended particulate organic carbon (POC) over a 1-yr period in White Clay Creek, a third-order stream in the southeastern Pennsylvania Piedmont, to assess temporal variability in seston concentration and quality at seasonal and diel timescales. Each month, we sampled stream water under baseflow conditions every 1.5 h over a 24-h period and measured seston and POC concentrations, carbon composition, pigment content, and 13 C isotopic ratios.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 45 publications
(74 reference statements)
2
31
1
1
Order By: Relevance
“…The most prominent temporal trend during our study was the autumn peak of PM in drift samples. Those observations diverge from results of seston research within Spanish (Molla et al 2006) and Pennsylvania (Richardson et al 2009) streams that evidenced peaking spring/summer PM concentrations, suggesting that spring/summer seston maxima might be a consequence of maximal stream organism activity (i.e., feeding and bioturbation) during warm seasons. In the previous study, Sertić Perić et al (2011) suggested that the autumn-peaking PM trend derives from the typical seasonal die-back of in-stream vegetation, and increased moss fragility caused by lack of protection by tufa accumulation during colder seasons.…”
Section: Patterns Of Particulate Matter Transportcontrasting
confidence: 52%
See 1 more Smart Citation
“…The most prominent temporal trend during our study was the autumn peak of PM in drift samples. Those observations diverge from results of seston research within Spanish (Molla et al 2006) and Pennsylvania (Richardson et al 2009) streams that evidenced peaking spring/summer PM concentrations, suggesting that spring/summer seston maxima might be a consequence of maximal stream organism activity (i.e., feeding and bioturbation) during warm seasons. In the previous study, Sertić Perić et al (2011) suggested that the autumn-peaking PM trend derives from the typical seasonal die-back of in-stream vegetation, and increased moss fragility caused by lack of protection by tufa accumulation during colder seasons.…”
Section: Patterns Of Particulate Matter Transportcontrasting
confidence: 52%
“…In the previous study, Sertić Perić et al (2011) suggested that the autumn-peaking PM trend derives from the typical seasonal die-back of in-stream vegetation, and increased moss fragility caused by lack of protection by tufa accumulation during colder seasons. Additionally, the PM loads increase in our study could be interpreted by seasonal changes within the deciduous riparian vegetation, and autumnal increase of allochtonous organic matter fall-in, respectively (Richardson et al 2009). …”
Section: Patterns Of Particulate Matter Transportmentioning
confidence: 99%
“…Isso sugere que outros fatores podem estar envolvidos, particularmente os relacionados às condições específi cas dos criadouros, uma vez que a precipitação e temperatura atmosférica atuam indiretamente sobre as comunidades aquáticas por meio de alterações na vazão e na temperatura da água dos cursos d'água (Shipp & Procunier 1986, Pistrang & Burger 1988, Gallardo-Mayenco & Toja 2002, Silk & Ciruna 2005 A investigação de um maior número de variáveis associadas direta e indiretamente às condições sazonais dos criadouros poderia defi nir com maior clareza os fatores que infl uenciam a composição taxonômica das assembléias de simulídeos ao longo do tempo, particularmente nas regiões tropicais. Além do fotoperíodo, da precipitação e da temperatura atmosférica, fatores ligados aos criadouros como vazão, temperatura da água, oxigênio dissolvido, pH e disponibilidade de recursos alimentares também devem ser analisados, uma vez que podem variar ao longo do tempo, infl uenciando a composição da fauna de macroinvertebrados (Thompson & Townsend 1999, Robinson et al 2002, Bunn et al 2006, Richardson et al 2009. Interações biológicas como competição e predação também podem estar envolvidas nas alterações de densidades populacionais de espécies de simulídeos ao longo do tempo (Malmqvist 1994).…”
Section: Padrões Temporaisunclassified
“…The watershed has 23% of total area as temperate deciduous forest largely within an intact riparian zone, 52% as pastures or hay fields, and 22% as row crop agriculture (Newbold et al 1997). At baseflow, WCC discharge averages 85 L s ; Newbold et al 1997), and between 0.1 and 0.4 mg suspended POC L -1 at baseflow (Richardson et al 2009). …”
Section: Site Descriptionmentioning
confidence: 99%
“…Suspended POC is likely a mixture of detrital organic matter particles with characteristic elemental and biochemical compositions that closely reflect their algal or vascular plant leaf sources and mineral-complexed organic matter that has a characteristic low C:N and protein-rich composition (Aufdenkampe et al 2007; Aufdenkampe et al 2011;Richardson et al 2009). Modeling results indicate that 88% to 94% of POC from this system is low-density detrital organic matter particles (leaf and algal carbon) while the remaining 6% to 12% of carbon is associated with high-density particles (Richardson et al 2009 From elemental and mixing model analyses, we calculated that about 30% of the detrital organic matter particles were composed of terrestrial vegetation while the remaining 70% were of algal origin (D. C. Richardson unpubl. data).…”
mentioning
confidence: 99%